The Effectiveness of Cooperative Learning NHT Type and Concept Mapping on the Cooperation and the Concept Master - Muhammad Hidayat; Paidi Paidi (Universitas Negeri Yogyakarta, 2019)
The study aimed to determine the effect of 1) cooperative learning model of numbered heads together (NHT) type on the cooperation ability and mastery of concepts of the students, 2) concept mapping on the cooperation ability and the mastery of concepts of the students, 3) the combination of cooperative learning of NHT type and concept mapping on the cooperation ability of the students, and 4) the combination of cooperative learning of NHT type and concept mapping on the mastery concept of the students of SMA N I Tidore Kepulauan. This research was a quasi-experimental study design using the nonrandomized control group pretest-posttest with three variations of the treatment and the control. The results were 1) Cooperative learning model of NHT type affects the students' ability to work, with the mean score of 32.3143 (very high), but it has no effect on the studentsˈ concept mastery, the mean pretest score of 61.1429 (high) and posttest score of 71.2857 (high). 2) Concept mapping does not affect the studentsˈ collaboration ability and their concept mastery, with mean pretest score of 62.9167 (high) and posttest score of 71.2500 (high). 3) The combination of the cooperative learning model of NHT type and concept mapping affects the cooperation ability, with the mean score of 33.2812 (very high). 4) The combination of the cooperative learning models of NHT type and concept mapping affects the concept mastery, with the score of 62.1875 (high) and the posttest score of 76.5625 (very high).